Pengaruh Religiusitas, Pemahaman Perpajakan, Status Sosial Ekonomi dan Love Of Money Terhadap Persepsi Penggelapan Pajak - Friska Ade Nauvalia; Yuniarti Herwinarni (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2018)
This study aims to examine the influence of religiusity, understanding taxation, socioeconomic status and love of money on the perception of tax evasion simultaneously and partially. Population in this study are accounting studens of economic faculty at the university of pancasakti tegal force of 2014 and 2015, with a sample of 81 students. Sampling technique used in this research in purposive sampling technique. The results of the analysis using computerized calculations with SPSS program version 22 which shows that religiosity, understanding taxation, socioeconomic status and love of money affect simultaneously to perceptions of tax evasion. Religusitas and socioeconomic status does not partially affect the perception of tax evasion. instead this study shows the understanding of taxation and love of money partially influence the perception of tax evasion.